2005
DOI: 10.1097/01.ana.0000181719.86978.05
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Midazolam as Oral Premedicant in Pediatric Neurosurgery

Abstract: In a randomized, double blind, placebo controlled study; the acceptability, efficacy and safety of injectable midazolam as oral premedicant in children was evaluated. One hundred children (ASA 1,2) aged 6 months to 6 years, undergoing elective neurosurgical operations, like meningomyelocele, meningo-encephalocele, ventriculo peritoneal and other shunts and craniotomies for tumour decompression etc., were included in the study. The patients were randomly assigned to one of four groups (A, B, C, D) receiving res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
(9 reference statements)
0
22
0
Order By: Relevance
“…In a study bySheta and Al Sarheed [14] apple syrup was used as a carrier. Mishra et al [17] mixed IV midazolam with honey [5 times the drug volume], which was well accepted by most of their subjects, in our study we have mixed midazolam with either flavoured paracetamol for oral preparation or with ketamine for nasal preparation. Adding paracetamol to oral preparation in addition to alleviating the bitter taste of midazolam it has analgesic effect, also many researchers recommended the addition of midazolam to ketamine to make use of ketamine as potent analgesic in the intraoperative as well as the postoperative analgesia and consequently decreasing postoperative agitation and speed up postoperative discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In a study bySheta and Al Sarheed [14] apple syrup was used as a carrier. Mishra et al [17] mixed IV midazolam with honey [5 times the drug volume], which was well accepted by most of their subjects, in our study we have mixed midazolam with either flavoured paracetamol for oral preparation or with ketamine for nasal preparation. Adding paracetamol to oral preparation in addition to alleviating the bitter taste of midazolam it has analgesic effect, also many researchers recommended the addition of midazolam to ketamine to make use of ketamine as potent analgesic in the intraoperative as well as the postoperative analgesia and consequently decreasing postoperative agitation and speed up postoperative discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Needleman et al 24 reported the incidence of vomiting as 8% in their studies when they used chloral hydrate together with hydroxyzine and N 2 O. Mishra et al 25 reported side effects such as nausea, vomiting, recovery agitation, and breathing depression following oral midazolam premedication at doses of 0.5, 0.75, and 1 mg kg À1 . In their study with 3 and 6 mg kg À1 ketamine, Gutstein et al 26 reported a significant increase in saliva secretion.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 100 cases indicated that oral midazolam was the most effective at 0.75 mg/kg while a dose of 0.5 mg/kg was less effective. Increasing the dose to 1.0 mg/kg did not show any advantages if compared to 0.75 mg/kg (18).…”
Section: Use Of Benzodiazepines In Pre-surgical Sedationmentioning
confidence: 71%